THE EFFECT OF INSTITUTIONAL REPUTATION, FINANCIAL LITERACY, AND ACCOUNTABILITY ON M U ZAKKI'S TRUST WITH SATISFACTION AS AN INTERVENING VARIABLE (STUDY ON BAZNAS OF BANTEN PROVINCE) - Nurul Safera; Itang Itang; Sulaeman Jajuli; Suryani Suryani; Syaeful Bahri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study uses satisfaction as an intervening variable in BAZNAS Banten Province to examine the influence of institutional reputation, financial literacy, and accountability on the trust of muzakki (payers of zakat). The phenomenon of many muzakki choosing to distribute zakat independently rather than through official institutions indicates that the level of public trust in zakat management institutions is still low, which is the main reason for conducting this study. This study combines quantitative methods with descriptive-verification strategies. A sample of 100 respondents was selected using purposive sampling, and data were collected through questionnaires. Analysis was conducted using multiple linear regression and mediation tests using the Baron & Kenny and Sobel Test techniques. The research findings indicate that zakat payers' satisfaction is significantly influenced by institutional reputation, financial knowledge, and accountability. Only financial knowledge and satisfaction were found to have a significant influence on zakat payers' trust in the second model; reputation and accountability did not show a significant influence. Furthermore, the relationship between financial literacy and zakat payers' trust is strengthened by zakat payers' satisfaction, which acts as an intermediary variable. Overall, this study suggests that the primary strategy in building zakat payers' trust at BAZNAS Banten Province is improving financial knowledge and service quality, which fosters satisfaction. These results can be used as a basis for developing zakat management regulations that are more accountable, transparent, and focused on the needs of zakat payers.